2022
DOI: 10.1523/eneuro.0386-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal, Multiscale Insights into Hippocampal Seizures Enabled by Transparent, Graphene-Based Microelectrode Arrays

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…To fully leverage the advantages of a three-compartment platform, suitable analysis tools for the obtained electrophysiological data must be designed. Analyzing network synchrony is crucial for obtaining a deeper understanding of epileptic seizure-like activity in vitro since it is suggested that neuronal network synchrony is a key factor in the onset and spread of seizures ( Jiruska et al, 2013 ; Ren et al, 2021 ; Mulcahey et al, 2022 ). In the context of the tripartite network circuitry model, by analyzing the synchronous patterns of firing within and between the interconnected local networks in vitro, one can identify interrelations of induced hyperactivity that may contribute to understanding the initiation and spread of epileptic seizures in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To fully leverage the advantages of a three-compartment platform, suitable analysis tools for the obtained electrophysiological data must be designed. Analyzing network synchrony is crucial for obtaining a deeper understanding of epileptic seizure-like activity in vitro since it is suggested that neuronal network synchrony is a key factor in the onset and spread of seizures ( Jiruska et al, 2013 ; Ren et al, 2021 ; Mulcahey et al, 2022 ). In the context of the tripartite network circuitry model, by analyzing the synchronous patterns of firing within and between the interconnected local networks in vitro, one can identify interrelations of induced hyperactivity that may contribute to understanding the initiation and spread of epileptic seizures in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Driscoll et al (2021) used transparent graphene microelectrode arrays and successfully recorded simultaneous high-bandwidth electrophysiology and calcium imaging signals of brain network activity induced by epileptic seizures in vivo. Moreover, these cellular-scale methods enable the recording of electrophysiology and calcium fluorescence in CA1 pyramidal neurons in hippocampus seizures (Mulcahey et al, 2022). Moreover, inspired by the accomplishments of brain studies, integrating a transparent graphene sensor onto a designed abdominal window detected changes in the activity of the enteric nervous system through simultaneous optical and electrical recording in a live mouse (Rakhilin et al, 2016).…”
Section: The Optical Property Of Graphene In Neural Imaging and Photo...mentioning
confidence: 99%